Contextual tumor suppressor function of T cell death-associated gene 8 (TDAG8) in hematological malignancies - Justus, Calvin R.; Sanderlin, Edward J.; Dong, Lixue; Sun, Tianai; Chi, Jen-Tsan; Lertpiriyapong, Kvin; Yang, Li V. (My University, 2017)
Background: Extracellular acidosis is a condition found within the tumor microenvironment due to inadequate blood perfusion, hypoxia, and altered tumor cell metabolism. Acidosis has pleiotropic effects on malignant progres‐ sion; therefore it is essential to understand how acidosis exerts its diverse effects. TDAG8 is a proton‐sensing G‐pro‐ tein‐coupled receptor that can be activated by extracellular acidosis. Methods: TDAG8 gene expression was analyzed by bioinformatic analyses and quantitative RT‐PCR in human hematological malignancies. Retroviral transduction was used to restore TDAG8 expression in U937, Ramos and other blood cancer cells. Multiple in vitro and in vivo tumorigenesis and metastasis assays were employed to evaluate the effects of TDAG8 expression on blood cancer progression. Western blotting, immunohistochemistry and biochemical approaches were applied to elucidate the underlying mechanisms associated with the TDAG8 receptor pathway. Results: TDAG8 expression is significantly reduced in human blood cancers in comparison to normal blood cells. Severe acidosis, pH 6.4, inhibited U937 cancer cell proliferation while mild acidosis, pH 6.9, stimulated its prolifera‐ tion. However, restoring TDAG8 gene expression modulated the U937 cell response to mild extracellular acidosis and physiological pH by reducing cell proliferation. Tumor xenograft experiments further revealed that restoring TDAG8 expression in U937 and Ramos cancer cells reduced tumor growth. It was also shown U937 cells with restored TDAG8 expression attached less to Matrigel, migrated slower toward a chemoattractant, and metastasized less in severe com‐ bined immunodeficient mice. These effects correlated with a reduction in c‐myc oncogene expression. The mecha‐ nistic investigation indicated that Gα13/Rho signaling arbitrated the TDAG8‐mediated c‐myc oncogene repression in response to acidosis. Conclusions: This study provides data to support the concept that TDAG8 functions as a contextual tumor sup‐ pressor down‐regulated in hematological malignancies and potentiation of the TDAG8 receptor pathway may be explored as a potential anti‐tumorigenic approach in blood cancers.